Remission from substance dependence: differences between individuals in a general population longitudinal survey who do and do not seek help() - Grella, Christine E. (2013)
BACKGROUND: Only a minority of individuals who have substance use disorders receives treatment, and those who do typically have more severe disorders. The current study examines the relationship of help-seeking with remission from alcohol and/or drug dependence and other outcomes. METHODS: Data from the Wave 1 (2001 – 2002) and Wave 2 (2004 – 2005) National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) were used to examine remission at Wave 2 among respondents who had past-year substance dependence disorders at Wave 1 (N=1,262). Multi-group structural equation modeling was used to compare individuals with (n = 356) and without (n = 906) prior help-seeking at Wave 1 on subsequent help-seeking and other factors that influence outcomes. RESULTS: Baseline help-seekers sought help at higher levels over the follow-up period (31% vs. 8%) and had lower rates of remission (50% vs. 68%), as compared with those without prior help-seeking, respectively. Among baseline help-seekers, there were stronger relationships between baseline stress and mental disorders and having sought help since baseline; age and past-year level of stress at follow-up; level of stress and health status at follow-up; and social support and mental disorders at follow-up. Among baseline non-help-seekers, there were stronger relationships between being female and past-year stress at follow-up, and between having sought help since baseline and physical health status at follow-up. CONCLUSIONS: Findings extend our understanding of the factors associated with recovery from substance dependence, including “natural recovery,” use of services outside of addiction treatment, and gender differences in help-seeking and remission.